Blood Microsampling for Complete Blood Count: Take Heed of Preanalytical Errors - Koscielniak, Barbara; Zajac, Andrzej; Tomasik, Przemysaaw (International Journal of Child Health and Nutrition, 2017)
Background: The credibility of the result of a complete blood count is closely connected with the preanalytical phase. Objectives: This study evaluated accordance of filling of microtubes with manufacturer’s recommendation and assessed the effect of storage of overfilled and underfilled samples on the results of complete blood count. Design and Methods: Volume of blood samples collected into microtubes in the wards of the University Children's Hospital in Cracow during one month was analyzed. In the stability studies, overfilled and underfilled samples stored at ambient temperature were analyzed at 1, 2, 3 and 12 hours after phlebotomy. The analysis was made using the SYSMEX XT-1800i analyzer. Results: More than half of the analyzed samples were incorrectly filled. 63% of the samples were filled above the manufacturer's recommended volume and 15% of test-tubes were filled below the recommendation. We observed differences between collected blood volume in accordance to the age of patients (p=0.001). The storage of overfilled and underfilled microtubes for complete blood count for 1,2,3 and 12 h at room temperature had no effect on the results of this test. Conclusion: Medical staff does not follow the instructions of the manufacturers. It might lead to a decrease of the quality and credibility of the results.